2010
DOI: 10.1124/jpet.110.165597
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Dependent Expression ofO6-Methylguanine-DNA Methyltransferase Gene Modulates Dacarbazine-Induced Hepatotoxicity in Mice

Abstract: O 6-methylguanine-DNA methyltransferase (MGMT) plays a crucial role in the defense against the alkylating agent-induced cytotoxic lesion O 6 -alkylguanine in DNA. Although a significant circadian variation in MGMT activity has been found in the liver of mice, the exact mechanism of the variation remains poorly understood. In this study, we present evidence that glucocorticoids were required for the 24-h oscillation of MGMT expression in mouse liver. The exposure of mouse hepatic cells (Hepa1-6) to dexamethason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…1D) Table S2). The functional analysis of the genes, done using KEGG database (6), showed that 12 biological pathways were enriched in a statistically significant manner (P < 0.05; Supplementary Table S3). Among these pathways, we further focused on the cell-cycle pathway because Atf4 À/À cells introduced with oncogenes resulted in G 0 -G 1 phase arrest (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1D) Table S2). The functional analysis of the genes, done using KEGG database (6), showed that 12 biological pathways were enriched in a statistically significant manner (P < 0.05; Supplementary Table S3). Among these pathways, we further focused on the cell-cycle pathway because Atf4 À/À cells introduced with oncogenes resulted in G 0 -G 1 phase arrest (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The overall incidence of grade 3-4 AEs was higher with ipilimumab plus DTIC compared with DTIC alone (56% versus 28%), as the rate of irAEs (38% versus 4%) [17]. Moreover, hepatic toxicity was increased with the addition of DTIC to ipilimumab compared with DTIC alone (overall incidence of transaminase elevation 29–33% versus 6%), possibly due to inherent hepatotoxicity of DTIC [73, 74]. Although rates of rash were consistent with expectations, there were lower rates of GI complications with no GI perforations and lower rates of endocrinopathy [17].…”
Section: Adverse Event Profile Of Ipilimumab Immunotherapy In Advamentioning
confidence: 99%
“…Oral administration of the same dosage of nutlin-3 into mice results in peak plasma concentration at 100 mmol/L (21). Similar reason was also applicable in both cases of bleomycin and dacarbazine (22,23). The viable cells were detected by staining with 5 mmol/L calcein-AM.…”
Section: Determination Of Cytotoxicitymentioning
confidence: 85%
“…The culture medium was replaced to drug-free medium, and cells were incubated for indicated times. The dosage of drugs was selected based on previous reports (20)(21)(22)(23). A significant antitumor effect of nutlin-3 is observed in mice when they were administered orally with the drug at the dosage of 200 mg/kg (20).…”
Section: Determination Of Cytotoxicitymentioning
confidence: 99%